2015
DOI: 10.1016/j.jbiomech.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of matrix-induced autologous chondrocyte implantation (MACI®) grafts in an equine model at 53 weeks

Abstract: There has been much interest in using autologous chondrocytes in combination with scaffold materials to aid in cartilage repair. In the present study, a total of 27 animals were used to compare the performance of matrix-assisted chondrocyte implantation (MACI®) using a collagen sponge as a chondrocyte delivery vehicle, the sponge membrane alone, and empty controls. A total of three distinct types of mechanical analyses were performed on repaired cartilage harvested from horses after 53 weeks of implantation: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 33 publications
(40 reference statements)
4
59
1
Order By: Relevance
“…In this study, we showed improvement in the compressive and frictional properties of the constructs but no change in the shear properties. While a few studies have characterized the frictional and shear properties of tissue engineered articular cartilage constructs cultured with bovine or porcine cells, this study is the first to perform such analysis on human chondrocyte‐seeded implants. Additionally, only a few previous studies have characterized the compressive properties of human chondrocyte seeded implants .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed improvement in the compressive and frictional properties of the constructs but no change in the shear properties. While a few studies have characterized the frictional and shear properties of tissue engineered articular cartilage constructs cultured with bovine or porcine cells, this study is the first to perform such analysis on human chondrocyte‐seeded implants. Additionally, only a few previous studies have characterized the compressive properties of human chondrocyte seeded implants .…”
Section: Discussionmentioning
confidence: 99%
“…Methods for analysis of the compressive properties of constructs in the murine model were based on those described previously [25]. Full thickness cylindrical plugs (3 mm diameter) were harvested from the constructs using a biopsy punch (Miltex, York, PA) applied perpendicular to the articular surface (n = 4-9…”
Section: Biomechanical Analysismentioning
confidence: 99%
“…IGF‐I transfection increased aggrecan and type II collagen content in cartilage repair and improved integration with surrounding cartilage matrix . Many studies have shown the benefits of grafts using autologous chondrocytes, but few have analyzed the mechanical properties of the repaired tissue . Particularly, there is little to no mechanical data on the restorative effects of IGF‐I in ACI grafts in a large animal model.…”
mentioning
confidence: 99%